Comparative genomic study on the complete plastomes of four officinal Ardisia species in China - Chunzhu Xie (Nature Portfolio, 2021)
Abstract Ardisia Sw. (Primulaceae) is naturally distributed in tropical and subtropical areas. Most of them possess edible and medicinal values and are popular in clinical and daily use in China. However, ambiguous species delineation and genetic information limit the development and utilization of this genus. In this study, the chloroplast genomes of four Ardisia species, namely A. gigantifolia Stapf, A. crenata Sims, A. villosa Roxb. and A. mamillata Hance, were sequenced, annotated, and analyzed comparatively. All the four chloroplast genomes possess a typical quadripartite structure, and each of the genomes is about 156 Kb in size. The structure and gene content of the Ardisia plastomes were conservative and showed low sequence divergence. Furthermore, we identified five mutation hotspots as candidate DNA barcodes for Ardisia, namely, trnT-psbD, ndhF-rpl32, rpl32-ccsA, ccsA-ndhD and ycf1. Phylogenetic analysis based on the whole-chloroplast genomes data showed that Ardisia was sister to Tapeinosperma Hook. f. In addition, the results revealed a great topological profile of Ardisia’s with strong support values, which matches their geographical distribution patterns. Summarily, our results provide useful information for investigations on taxonomic differences, molecular identification, and phylogenetic relationships of Ardisia plants.